Pledgee competition, strategic disclosure, and future crash risk - Xiaoxi Li; Jing Liu; Kemin Wang (China Journal of Accounting Research, 2019)
We investigate whether pledgee competition affects the disclosure choice of firms whose controlling shareholders pledge their shares. We find that pledgee competition is positively related to pledge firms' annual report tone management. This positive relationship is stronger for pledge firms with lower credit quality and non-state-owned enterprise pledge firms. Further corroborating our results, higher pledgee competition increases the future crash risk of pledge firms. Collectively, our results suggest that competition pressure induces pledgees to lower their monitoring incentives to remain competitive in the marketplace, thus leading to pledge firms' bad news hoarding behavior.
Keywords: 650; Pledgee competition; Share pledge; Tone management